TAX ASSIGNMENT IN SELECTED FEDERATIONS: LESSONS FOR NEPAL - Chhetry, Dil Bahadur (PEOPLE: International Journal of Social Sciences, 2017)
The Constitution of Nepal promulgated on September 20, 2015 has transformed the country from the unitary system of governance to a federal democratic republic. The constitution has provisioned the powers and responsibilities to the federal, state, and local governments under the schedule 5, 6 and 8 respectively. However, it has provisioned the concurrent powers of the federation and State under the schedule 7 and federation, state and local level under the schedule 9. The objective of this article is to review the revenue assignment modality provisioned in the present constitution and to suggest for further amendment based on the international practices and national need. Regarding the issue, the paper suggests that- besides the existing provision of constitution, payroll tax should be assigned to the state governments and excise duties (Licence Fee) on alcoholic beverage and tobacco at consumption level should be collected by the sub national governments after their legal and institutional setup and enhancing their capacity of tax administration. This can be helpful in order to reduce vertical fiscal imbalances. Furthermore, Value Added Tax (VAT) should be collected at both the federal and state levels concurrently in future after developing the revenue mobilization capacity of the state governments which also contributes to minimize the vertical fiscal imbalance. In future, the state and local governments should also explore the additional tax bases.JEL Classification: H21, H22, H23, H24, H25